Litter Fall in A Primary and Two Logged-over Lowland Tropical Rainforests in Pasirmayang, Jambi. - UPIK ROSALINA WASRIN; AGUS EKA PUTERA (BIOTROPIA, 1999)
Litter accumulation in a  primary and a logged-over  lowland dipterocarp  forest at Pasirmayang, Jambi was measured using the litter trap method. In the primary forest, traps were placed in four distinct areas, reflecting the succession stages of the forest from building to maturation. In the logged-over forest, litter production was measured at two different sites, one cut in 1979/1980 and the second in 1983/1984. In the primary forest, average litter production during the observation period was 925 g m"2yr'. In the logged-over forest, average litter production was 721 g m'2 yr1 for the site cut in 1979/1980 and 706 g m'2 yr1 for the site cut in 1983/1984. Leaves comprised the major contributor of litter with 67% of total litter produced in the primary forest, 67% of total litter in the 1979/1980 cut logged-over forest, and 65% of total litter in the 1983/1984 cut logged-over forest. The purpose of the study was  to use litter fall as a measure of forest productivity  to assess the recovery of logged-over forests and, to provide a basis for comparison of forest-derived land practices for appropriate forest management strategies. Key words: Litter production/primary forest/logged-over forest/forest productivity/Pasirmayang/Jambi.